EMOTIONAL WELL-BEING IN SCHOOLS - Elksne, Gunita; Rubene, Zanda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The goal of the paper was to research the emotional well-being of students, teachers, and factors that impact it using quantitative research methods. Research was a case study and reflects a situation in one particular school. Emotional well-being plays an important role in personality development. Presence or absence of emotions like joy, satisfaction, trust, and reliance determines the perception, thinking, and actions of students. Positive emotions cause energetic and functional mobilization of the central nervous system and the whole human organism, promotes purposeful actions by connecting cognitive processes with fulfillment of student’s current needs. Emotions either enable or disable the learning process for a student. If positive emotions are absent, brain is in a passive state - active learning starts when emotions activate the brain. The impact of emotions on a student in the learning process can be mainly observed through attention that is payed towards studying; however, positive emotions that are connected to studying can also promote student’s interest in the study subject. Positive emotions can encourage several abilities like interest, enthusiasm, optimism, loyalty and the motivation to act. In addition, thinking can also be enabled, as well as an improvement in the ability to learn new things. These abilities make the learning process more productive. As a large part of students day is spent at school their emotional well-being is directly related to emotional well-being of pedagogues. It is crucial that a pedagogue is able to be aware of their own emotions and feelings and knows how to accept them and use them in solving pedagogical situations, as well as improving of his/her own life while still acting within professional ethical norms.